IMPLEMENTATION OF E - COMMERCE IN MEDIA PROMOTION FOR SMALL AND MEDIUM BUSINESS REVENUE INCREASE PRODUCTION DISTRICT BANYUMAS - Wati, Hidayah (Bappeda Kabupaten Pringsewu, 2016)
Small and Medium Enterprises is a prayer One thing Sector That contributed significantly spur growth hearts Economics. Industrial patchwork is a prayer One attempt Engaged hearts Sector About Making crafts. The SMEs were in the village Sukamulya District of Banyumas has Many Problems of which is System Marketing And Promotions Still BY users rely on marketing through agents and Come Directly bring examples with consumer Product Candidate Into that Product Sales Still Limited hearts promote and market their products. Troubleshooting to review the Author MAKE e-commerce site then MAKE some Diagram That Represent data flow diagrams (Flowchart), context diagrams, and Data Flow Diagrams, followed WITH designing web using PHP and database programming language. Article Search Google on sme E-commerce in the district of Banyumas Rag can be helped promote and market their hearts findings completely craft industry patchwork that can be shown to the introduces 'community Size about Products Yang has produced.